Spontaneous reduction of prolactinoma post cabergoline withdrawal - Sampath Kumar Venkatesh; Deepak Kothari; Smita Manchanda; Anil Taneja; Bindu Kulshreshtha (Indian Journal of Endocrinology and Metabolism, 2012)
Prolactinomas are common pituitary tumors usually highly responsive to dopamine agonists. Around 70-90% of the prolactinomas exhibit decrease in tumor size, though variably with these agents. Uncommonly, there may be little or no shrinkage in pituitary tumor. In the absence of medical therapy, pituitary apoplexy may also result in tumor shrinkage, albeit rarely. We report here a case showing only modest reduction in prolactinoma with cabergoline given for a period of one and a half years. Surprisingly, this tumor showed a 40% reduction in the tumor size 3 months after cabergoline withdrawal in the absence of clinical or radiological evidence of apoplexy.